Vertical organic field effect phototransistor with two dissimilar source and drain contacts - Woon, K.L.; Yeo, G.N. (Elsevier, 2014)
A solution processable vertical organic field effect phototransistor was fabricated using poly(3-hexylthiophene) and 1-(3-methoxycarbonyl)propyl-1-phenyl[6,6]C61 as the photo-active materials while poly(methyl methacrylate) is used as a dielectric layer. Interdigitated conductive poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) is used as a source and lithium flouride/aluminum as a drain. The device exhibits current modulation when the gate is positively biased. A significant photoeffect is observed in the reverse bias mode. Unlike conventional organic phototransistors, this device can operate at a zero source–drain bias with a photosensitivity and responsivity proportional to the gate voltage. A photosensitivity of up to 105 and a responsivity of up to 2 AW− 1 are achieved in this mode. This effect is due to the presence of the weak photovoltaic behavior of this device.